Performance parameters of ETICS: Correlating water resistance, bio-susceptibility and surface properties. (22nd February 2021) - Parracha, J.L.; Borsoi, G.; Flores-Colen, I.; Veiga, R.; Nunes, L.; Dionísio, A.; Gomes, M. Glória; Faria, P.
Graphical abstract: Highlights: Assessment of water resistance, mould susceptibility and surface properties of ETICS. Moisture content influence on the thermal conductivity of the insulation layer. Definition of ETICS performance parameters. Contribution towards the development of ETICS with improved durability. Abstract: The use of External Thermal Insulation Composite Systems (ETICS) significantly increased in the last decades due to their enhanced thermal properties, low installation cost and ease of application, not only in new constructions but also for thermal retrofitting of building facades. These multilayer rendering systems are constantly exposed to weathering agents and anthropic factors which can lead to physical-mechanical and aesthetical anomalies and thus affect their durability. However, possible synergetic effects among these agents are often neglected by international technical documents on the evaluation of the effectiveness and durability of ETICS. With the aim of filling this gap, moisture transport properties (capillary water absorption, water vapor permeability, water absorption under low pressure, and drying kinetics), thermal conductivity, mould susceptibility and surface properties (color, gloss, and roughness) of twelve commercially available ETICS were assessed and discussed. Possible links between these factors were analyzed and ETICS performance parameters were defined. Results demonstrate that a deeper knowledge of the correlation among ETICS properties can effectively contribute to the evaluation of the efficiency and long-term durability of these systems.